Occupational lead exposure in Finland. V. Shipyards and shipbreaking. - Tola, Sakari; Karskela, Veikko (Scandinavian Journal of Work, Environment & Health, 1976)
Three Finnish shipyards and two shipbreaking enterprises were studied for lead exposure. Blood lead (Pb-B) concentration was measured for 568 workers in the shipyards and 13 workers in the shipbreaking enterprises. Erythrocyte delta-aminolevulinic acid dehydratase (ALAD) activity was determined for 139 workers in one shipyard and 7 workers in one shipbreaking enterprise. Hemoglobin level was determined for 545 workers in the three shipyards and 7 workers in one shipbreaking enterprise. Lead exposure in the shipyards was relatively low. No Pb-B value exceeded 70mug/100 ml. The most exposed occupations were welders, plumbers, painters, repairmen, and sheet metal workers. The mean Pb-B did not exceed 40 mug/100 ml in any of these groups. In both shipbreaking enterprises one Pb-B value exceeded 70 mug/100 ml, the mean Pb-B values of all the workers in the two enterprises being 51 and 46 mug/100 ml. respectively. ALAD values corresponded well with the respective Pb-B values. All the hemoglobin mean values were normal, and there were no statistically significant differences between the hemoglobin values of different groups.
Keywords: blood; delta-aminolevulinic dehydratase; Finland; lead; lead exposure; occupational lead exposure; shipbreaking; shipyard